Womanliness Construction as Postmodernist Fiction in Caryl Churchill’s Top Girls - Dita Ayu Maharani (Fakultas Ilmu Budaya, 2025)
In postmodernist fiction, narrative is no longer seen as a single thing, but as something diverse, including the narrative of womanliness. This study examines how the narrative of womanliness in Caryl Churchill's Top Girls is constructed through various women's experiences that are presented with a non-linear narrative structure. The female characters in this play come from different times, cultures, and backgrounds, which each of them bring experiences and challenges that reflect the social conditions of their time. Through McHale's three-dimensional model adapted from Hrusovski, this play shows that the worlds built in the text support the diversity of narratives of womanliness. This is also strengthened by the words in the play that create constructions of meaning regarding the role of women in society. Therefore, Brian McHale's postmodernist fiction theory is used as a strategy to analyze the construction of womanliness presented in Top Girls regarding women's diverse experiences
Reaploud Repository February_Hasyim
Keywords: the narrative of womanliness; postmodernist fiction; Top Girls